2019
DOI: 10.1016/j.cortex.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity in struggling readers before intervention relates to future reading gains

Abstract: Neural markers for reading-related changes in in response to intervention may represent biomarkers that could inform intervention plans as a potential index of the malleability of the reading network in struggling readers. Particularly interesting is the role of activation outside the reading network, especially in executive control networks important for reading comprehension. However, it is unclear whether any intervention-related executive control changes in the brain are specific to reading tasks or reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 110 publications
0
31
1
1
Order By: Relevance
“…For the Twin study sample, we analyzed data from one twin randomly selected from each twin pair, originally collected as part of the Texas Twin Project ( Engelhardt et al, 2019 ; Harden et al, 2013 ). For the Reading Study ( Nugiel et al, 2019 ; Roe et al, 2018 ), we lowered the performance criteria to allow for greater variability in performance and to have consistent criteria across the three studies used here. We also excluded any participants from the original Reading Study sample that had clinical diagnoses of dyslexia or attention-deficit/hyperactivity disorder; our Reading Study sample here included some participants who were labeled as struggling readers by scoring below a cutoff on school administered reading tests.…”
Section: Methodsmentioning
confidence: 99%
“…For the Twin study sample, we analyzed data from one twin randomly selected from each twin pair, originally collected as part of the Texas Twin Project ( Engelhardt et al, 2019 ; Harden et al, 2013 ). For the Reading Study ( Nugiel et al, 2019 ; Roe et al, 2018 ), we lowered the performance criteria to allow for greater variability in performance and to have consistent criteria across the three studies used here. We also excluded any participants from the original Reading Study sample that had clinical diagnoses of dyslexia or attention-deficit/hyperactivity disorder; our Reading Study sample here included some participants who were labeled as struggling readers by scoring below a cutoff on school administered reading tests.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is associated with visual orthographic and lexical-semantic processing (Kawabata Duncan et al, 2014 ; Thuy et al, 2004 ). A previous study has reported that enhanced right FG activity during a reading task is associated with reading gain in English-speaking children who struggle with reading (Nugiel et al, 2019 ). In addition, the left PrCG is involved in handwriting (Longcamp et al, 2019 ; Roux et al, 2009 ) and Japanese children learn to read and write Kanji by intensive handwriting repetition (Naka and Naoi, 1995 ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, a sentence reading task activated regions implicated in both reading and EF demand, and some EF‐related brain regions did correlate with reading ability (Roe et al., ). Activation of some of these regions also predicted a positive intervention response (Nugiel et al., ). As such, the findings are consistent with a recent study (Aboud, Barquero, & Cutting, ) that found that activation of both reading and cognitive control regions during a lexical decision task predicted intervention response in a group defined with poor decoding.…”
Section: Discussionmentioning
confidence: 99%